Cytotoxic effects of Benzodioxane, Naphthalene diimide, Porphyrin and Acetamol derivatives on HeLa cells - Shareni Jeyamogan; Naveed Ahmed Khan; Ayaz Anwar; Muhammad Raza Shah; Ruqaiyyah Siddiqui (SAGE Open Medicine, 2018)
Objectives: To synthesize novel compounds belonging to Benzodioxane, Naphthalene diimide, Aminophenol derivatives and Porphyrin classes and test their potential anticancer properties. Methods: Several compounds were synthesized and their molecular identity was confirmed using nuclear magnetic resonance. Potential anticancer properties were determined using cytopathogenicity assays and growth inhibition assays using cervical cancer cells (HeLa). Cells were incubated with different concentrations of compounds belonging to Benzodioxane, Naphthalene diimide, Aminophenol derivatives and Porphyrins and effects were determined. HeLa cells cytopathogenicity was determined by measuring lactate dehydrogenase release using cytotoxicity detection assay. Growth inhibition assays were performed by incubating 50% semi-confluent HeLa cells with Benzodioxane, Naphthalene diimide, Aminophenol derivatives and Porphyrin compounds and HeLa cell proliferation was observed. Growth inhibition and host cell death were compared in the presence and absence of drugs. Results: Cytopathogenicity assays showed that the selected compounds were cytotoxic against HeLa cells, killing up to 90% of cells. Growth inhibition assays exhibited 100% growth inhibition. These effects are likely via oxidative stress, production of reactive oxygen species, changes in cytosolic and intracellular calcium/adenine nucleotide homeostasis, inhibition of ribonucleotide reductase/cyclooxygenase and/or glutathione depletion. Conclusions: Benzodioxane, Naphthalene diimide, Aminophenol derivatives and Porphyrins exhibited potent anticancer properties. These findings are promising and should pave the way in the rationale development of anticancer drugs. Using different cancer cell lines, future studies will determine their potential as anti-tumour agents as well as their precise molecular mode of action.